ROLE OF MUSIC ON PSYCHOLOGY OF SHOPPERS IN RETAIL ORGANIZATIONS - Anute, Nilesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research explores the impact of background music on consumer perceptions and buying behavior in retail settings, aiming to uncover its strategic implications for store management. A quantitative approach was adopted, surveying 288 retail shoppers to gauge their perceptions and behaviors in response to background music. Findings indicate a strong positive correlation between the presence of music and enhanced shopping experiences, enjoyment, and alignment with brand image. Respondents reported that music influenced their decision to stay longer, make unplanned purchases, and perceive product quality more favorably. These findings highlight music’s role beyond ambiance, serving as a potent tool for influencing consumer emotions and behaviors in retail environments. The study concludes with implications for retail practitioners, emphasizing the importance of strategic music selection to create favorable shopping atmospheres and foster customer satisfaction and loyalty.